A computational characterization of H2O2@C60. Issue 2 (1st February 2022) - Slanina, Zdeněk; Uhlík, Filip; Adamowicz, Ludwik; Pan, Changwang; Lu, Xing
ABSTRACT: The hydrogen-peroxide encapsulation into C60 is evaluated using the DFT (M06-2X) and B2PLYPD as well MP2 calculations in the standard 6-31++G** and 6-311++G** basis sets. The H2 O2 encapsulation is attractive, yielding an energy gain of about 12 kcal/mol. Such substantial encapsulation energy could allow for the high-temperature and high pressure synthesis (originally used for encapsulation of rare gases in fullerenes) of H2 O2 @C60 which has otherwise been observed only in a form of encapsulation into an open-cage C60 derivative. The calculated structural characteristics and IR vibrational spectrum are presented, too.